2017
DOI: 10.12932/ap-020317-0039
|View full text |Cite
|
Sign up to set email alerts
|

Needle length for epinephrine prefilled syringes in children and adolescents: Is it one inch?

Abstract: Background: Intramuscular epinephrine is the first line drug in the treatment of anaphylaxis. This study was to identify the appropriateness of 1 inch needle length for epinephrine prefilled syringes in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…26,27 However, in another paediatric study where a slightly longer needle was used as the reference (25.4 mm), again with no pressure being applied during USS, the risk of periosteal/IO injection was as high as 12% in those aged 2-5 years. 32 Apart from needle length, the other risk factors for adrenaline being administered SC, and not IM, were an increased BMI 6,25,26,28,29,[32][33][34] and female sex for adults (independent of BMI). 6,29,33 Johnstone et al 29 reported in their study that 87% of females were at risk of SC injection compared to 0% of males.…”
Section: Imaging Studiesmentioning
confidence: 99%
“…26,27 However, in another paediatric study where a slightly longer needle was used as the reference (25.4 mm), again with no pressure being applied during USS, the risk of periosteal/IO injection was as high as 12% in those aged 2-5 years. 32 Apart from needle length, the other risk factors for adrenaline being administered SC, and not IM, were an increased BMI 6,25,26,28,29,[32][33][34] and female sex for adults (independent of BMI). 6,29,33 Johnstone et al 29 reported in their study that 87% of females were at risk of SC injection compared to 0% of males.…”
Section: Imaging Studiesmentioning
confidence: 99%